CSS for Everybody : From Beginner to Boss - Taulien, Kalob (Packt Publishing, 2021)
Make websites that look beautiful and work on any device types About This Video Learn CSS from the basics to build aesthetically pleasing web pages Learn advanced features in CSS such as animations and transitions Build responsive web pages that look amazing on any device In Detail In the first section of the course, we'll learn about CSS syntax, how to style certain HTML elements using CSS selectors, changing the text on our page, using different colors, changing default link styling, adding background images, working with borders, changing heights and widths of elements, changing spacing with margins and paddings, and making parts of your page see-through. In the second section, we'll apply everything we learned in CSS 101 and get our hands dirty with more advanced CSS. This includes understanding the display property, the box model, outlines versus borders, specific element positioning, advanced CSS selectors, pseudo selectors and pseudo-elements, transitions, animations, flexbox, and CSS grid. In the final section, we'll learn about responsive web design. This is how we make websites look great on all devices, including phones, tablets, laptops, desktops, TVs, and more. We'll also dive right into media queries and what mobile-first means and why it's important. Then we'll make images and video embeds responsive. And we'll finish the course with a final project where you make a flexbox (or CSS grid) page layout and then transform it into a responsive website so that it looks amazing on smaller devices, such as a phone.